DNA-GENEALOGY OF PRESENT-DAY HUMANS - Помогайбо, В.М.; Власенко, Н.О.; Березан, О.І.; Петрушов, А.В.; Беседіна, І.С.; Починок, Є.А.; Мельничук, М.М.; Макаренко, Я.М. (World of Medicine and Biology, 2016)
Results of the DNA researches concerning structural peculiarities of people living in different parts of the world have confirmed the hypothesis of the African origin of contemporary humanity that had been based only on the archaeological and paleontological data before. It was shown that the present-day humans had come from the population, numbering 2 000 to 10 000 individuals, that existed on the territory of South-East Africa about 190 thousand years ago. Migration of our remote ancestors from Africa and their succeeding colonization of the planet had been taking place within the period of 100 – 50 thousand years. It was also found out that the Neanderthal man and the man of the present-day anatomical type are related species that had come from the common ancestor. Contemporary humanity is the common biological species consisting of large races that had originated in different continents under the influence of different biological, geographic, weather and climatic factors.